Innovative Approaches to the Thermal Conductivity Tensor in Ionospheric Plasma of the Northern Hemisphere's F-region - Yasar, Mehmet (Pleiades Publishing Ltd, 2025)
This study aims to investigate the energy transfer mechanisms and the behavior of thermal conductivity of this region by examining the thermal conductivity coefficients calculated for critical altitudes in the F region of the ionosphere. Electron-ion collisions and the geometry of the magnetic field affect these coefficients. The thermal conductivity in the ionosphere can exhibit anisotropic properties (different values in different directions) due to the directional dependence of the Earth's magnetic field. Theoretical approaches have been used and numerical calculations have been performed to analyze the thermal conductivity of the ionosphere. The findings indicate that the magnitudes of the thermal conductivity coefficients were at the level of electrical conductivity and the tensor elements (Kzx, Kxz, Kyz, Kzy) were negative, while the Kyx, Kxy elements were positive up to the equator and then became negative. This phenomenon, called effective thermal conductivity, is not actually a negative value for thermal conductivity, but rather an unusual situation resulting from the direction-dependent effect of the magnetic field. It has been determined that the magnitudes of the tensor elements on March 21 are slightly greater than those on September 23.
Keywords: the earth ionosphere; average thermal conductivity coefficients; the northern hemisphere; ionospheric equinox changes